Dynamics of sandbanks and dunes of continental shelf in macro-tidal environment: Example of the banc du four (Western Brittany, France) - Franzetti, Marcaurelio (CCSD, 2014)
Submarine dunes and sandbanks constitute the major sedimentary structures of continental shelves subjected to a macrotidal regime. Dunes are of medium size, with crests perpendicular to the currents that generate them, whereas sandbanks are larger in size, with crests parallel to the currents.The northern part of the Iroise Sea is a section of the Breton continental shelf swept by powerful tidal currents and stirred by strong ocean swells from the North Atlantic. The seafloor in this area presents a sandy structure that, until now, had only been described in a summary manner, consisting of a sandbank and a few dunes covering a very limited area: the Banc du Four.A first ultra-high-resolution bathymetric survey was conducted in the area in 2009, revealing a much larger (10x20 km²) and more complex sedimentary structure with several unique characteristics. The Banc du Four consists of a sandbank flanked by two dune fields, eastern and western, pointing respectively towards the northeast and northwest, giving the entire structure a V-shape.The bank represents a sand volume of 250 million cubic meters (4x2 km² and 45 meters thick), composed of five major internal units that indicate a multiphase construction. This process began 14,000 years BP and was mainly driven by changes in the physiography of the area during the last eustatic sea-level rise. The sandbank appears to be more evolved at present.At the Banc du Four, more than 500 dunes have been observed, displaying all sizes and shapes recorded at other study sites. The morphodynamics of the dunes is highly active even at great depths (>70 meters), with migration rates reaching up to 20 m/year. The dune dynamics highlight the importance of a multidisciplinary approach (internal and external morphologies, sediment composition, hydrodynamics), challenging certain parametric morphological relationships used to predict dune movement.This study also allowed the observation and description of an erosion-deposition process that explains the formation of certain ...